2017
DOI: 10.1021/acsomega.7b00838
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Soft Nanotubes Derivatized with Short PEG Chains for Thermally Controllable Extraction and Separation of Peptides

Abstract: By means of a two-step self-assembly process involving three components, including short poly(ethylene glycol) (PEG) chains, we produced two different types of molecular monolayer nanotubes: nanotubes densely functionalized with PEG chains on the outer surface and nanotubes densely functionalized with PEG chains in the nanochannel. Turbidity measurements and fluorescence spectroscopy with an environmentally responsive probe suggested that the PEG chains underwent dehydration when the nanotubes were heated abov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…We used a two‐step coassembly process to construct a series of seven different monolayer nanotubes through hydrophobic interactions and the formation of multiple intermolecular hydrogen bonds ( Table 1 ). First, as previously reported, we used the coassembly process to construct two nonionic nanotubes with an inner diameter of 8 nm, which we called inPEG‐wide‐NT and outPEG‐wide‐NT. inPEG‐wide‐NT was constructed from an asymmetric bolaamphiphile with a d ‐glucose head group at one end and a hydroxyl head group at the other end ( 1(16, OH) ), a glycolipid including a d ‐glucose unit ( 2(16) ), and a PEG derivative conjugated with a glycylglycine (GlyGlyPEG 8 ) ( Figure , left); and the resultant nanotube had a dense layer of short PEG chains on the inner surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a two‐step coassembly process to construct a series of seven different monolayer nanotubes through hydrophobic interactions and the formation of multiple intermolecular hydrogen bonds ( Table 1 ). First, as previously reported, we used the coassembly process to construct two nonionic nanotubes with an inner diameter of 8 nm, which we called inPEG‐wide‐NT and outPEG‐wide‐NT. inPEG‐wide‐NT was constructed from an asymmetric bolaamphiphile with a d ‐glucose head group at one end and a hydroxyl head group at the other end ( 1(16, OH) ), a glycolipid including a d ‐glucose unit ( 2(16) ), and a PEG derivative conjugated with a glycylglycine (GlyGlyPEG 8 ) ( Figure , left); and the resultant nanotube had a dense layer of short PEG chains on the inner surface.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that inPEG-wide-NT and outPEG-wide-NT were able to not only extract but also back-extract hydrophobic amino acids from/into bulk solutions in accordance with the dehydration and rehydration of the PEG chains. [10] We speculated that this property of the nanotubes may be useful for chiral separation of amino acids because the nanotubes have supramolecular chirality conferred by their chiral d-glucose unit. To fluorescently detect the chiral separation of amino acids and enhance their hydrophobicity, we labeled amino acids with 4-fluoro-7-nitorobenzofurazan (NBD).…”
Section: Chiral Sensing Via Extraction and Back-extractionmentioning
confidence: 99%
“…Supramolecular nanotubes with controllable diameters and functionalizable surfaces formed by self‐assembly of rationally designed synthetic amphiphiles in solvents exhibit several biomimetic functions, including the stabilization of proteins and DNA under harsh conditions, acceleration of protein refolding, and chiral separation of peptides . Recent studies revealed that morphological transformation of the nanotubes into other structures having no cavities[6f] or the contraction of nanotube channels in response to external stimuli allows the nanotubes to aggressively release the encapsulated molecules into bulk solution.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular polymerization of macrocycles [1][2][3][4][5][6] offers a means to design nanotubes with distinct interior environments for chemical separations, 7,8 selective ion transport, [9][10][11] energy storage, 12,13 or size-selective catalysis. 14,15 However, many of these assemblies rely on weak cohesive interactions that are disrupted by minor structural variations, elevated temperatures, or mechanical stress.…”
Section: Introductionmentioning
confidence: 99%